2012
DOI: 10.1038/onc.2012.142
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model with T58A mutations in Myc reduces the dependence on KRas mutations and has similarities to claudin-low human breast cancer

Abstract: Expression of c-Myc is highly prevalent in human breast cancer and stability of the oncoprotein is regulated through Ras-regulated phosphorylation at serine 62 and threonine 58. Previous studies have illustrated the importance of accumulation of KRas mutations in Myc-mediated tumor formation. To examine Myc dependence upon Ras mutations we have generated MMTV regulated Myc and Myc T58A transgenic mice. Expression of the more stable T58A Myc allele resulted in a reduction in KRas-activating mutations. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 30 publications
(52 reference statements)
3
30
0
Order By: Relevance
“…However, the initial euphoria quickly morphed into exploring the causal role of claudin proteins in neoplastic growth and progression. These queries were fueled by generation of mice, genetically modified for specific claudin proteins, and subjected to mouse models of carcinogenesis [23, 24, 47, 48]. Outcome from these investigations and from in vitro manipulations in cancer cells has landed strong support for the causal role of claudin proteins in regulating carcinogenic processes [9, 27, 30, 51].…”
Section: Introductionmentioning
confidence: 99%
“…However, the initial euphoria quickly morphed into exploring the causal role of claudin proteins in neoplastic growth and progression. These queries were fueled by generation of mice, genetically modified for specific claudin proteins, and subjected to mouse models of carcinogenesis [23, 24, 47, 48]. Outcome from these investigations and from in vitro manipulations in cancer cells has landed strong support for the causal role of claudin proteins in regulating carcinogenic processes [9, 27, 30, 51].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a more detailed characterization of a larger number of p53 null tumors revealed a variety of subtypes with strong similarities to human breast cancer [11], revealing the importance of examining a large number of samples to capture tumor heterogeneity and variability. Further, expanding the number of Myc induced tumors revealed that a subpopulation of Myc induced tumors had similarities to claudin-low human breast cancer [19]. Taken together, recent comparative studies [11,17,19-22] highlighted a clear need for a comprehensive examination of the genomic features of mouse models of breast cancer and their relation to human breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Further, expanding the number of Myc induced tumors revealed that a subpopulation of Myc induced tumors had similarities to claudin-low human breast cancer [19]. Taken together, recent comparative studies [11,17,19-22] highlighted a clear need for a comprehensive examination of the genomic features of mouse models of breast cancer and their relation to human breast cancer. To this end, we assembled an expansive dataset of mouse models of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the T58A point mutant is more transforming than wild-type (WT) MYC in both cell line and in vivo models, which has been attributed to both an increase in protein stability and decreased apoptosis (8)(9)(10)(11)(12)(13). Furthermore, a recent report using the MMTV-MYC transgenic model found fewer activating mutations in RAS when T58A was expressed compared with the WT allele (14), highlighting how gain-offunction phosphorylation mutants of MYC can be used to understand the cooperating pathways contributing to transformation. Clearly, signaling through T58 is an important mechanism to negatively regulate MYC-induced transformation and the T58A gain-of-function mutant has been an important experimental tool to understand signaling regulating MYC activity.…”
Section: Introductionmentioning
confidence: 99%